Kriz döneminde habercilik : Covid-19 salgını sürecinde Fas ve Fransız medyasında yayınlanan haberlerin karşılaştırmalı analizi - Brouk, Ouijdane (My University, 2022)
Çin’de 31 Aralık 2019 tarihinde, dünyayı çok etkileyen bir salgın ortaya çıkmıştır. İlk olarak Wuhan kentinde çıkan Covid-19 olarak adlandırılan öldürücü virüs, dünyayı alarma geçirdi. Başta Avrupa, Amerika ve Arap ülkeleri olmak üzere, yeni tip Coronavirus ( Covid-19) dünya çapında bir kabus haline geldi. Ülkelerin ekonomisi, sosyal hayatı ve altyapısı fark etmeksizin, tüm dünyayı etkiledi. Bu sırada medya, halkın ana bilgi kaynağı oldu. Her ülke, yapılan habercilik yoluyla, geniş kitlelere ulaşmaya ve halkı bilgilendirmeye çalıştı. Farklı platformlarda habercilik yapan gazeteciler, hassas bilgileri aktarırken kritik bir rol oynamaktadır. Coronavirus salgının ilk ortaya çıktığı andan itibaren, salgının sebebinden, tedavi bulmak için süren çalışmalara kadar binlerce haber yapıldı. Bu bağlamda, söz konusu çalışmada da Corona dönemindeki habercilik ve özellikle yayınlanan metin ve görüntüler üzerinde durulacaktır. Coronavirus salgınının ortaya çıkmasıyla dünya çapında virüse ilişkin haberler çok izlendi. Herkes büyük bir dikkatle, dünyada yaşanan krizi evinden takip etti. Kitleler radyo, televizyon, gazete veya internet gibi farklı kaynaklardan doğru bilgi edinmek için çabaladı. Tüm bunlar doğrultusunda, çalışmada, Coronavirus krizinde habercilik alanında yaşanan gerginlik bağlamında yayınlanan haberler karşılaştırılacaktır. Bu perspektifle de Fas ve Fransa ülkeleri örneklem olarak seçildi. Bununla birlikte, şunu da göz ardı etmemek gerekir ki söz konusu kriz döneminde, herhangi bir bilgi yanlış anlaşılırsa halkın davranışları etkilenebilmekte ve bu da salgın sürecini olumsuz etkileyebilmektedir. Bunun önemini bilen farklı ülkelerdeki medya kuruluşları da salgının durumuna göre yayınlar yapmaya çalıştı. Bu bağlamda da Corona döneminde yayınlanan haberlerin incelenmesi kriz dönemlerindeki haberciliğin rolünü anlamak adına önemlidir.

At the end of 2019, while the world was preparing to welcome a new year, nobody was thinking that it's going to be a year full of curfews, quarantine, and lockdowns. December 2019, Coronavirus (Covid -19) one of the most affected and deadly viruses in history has appeared in Wuhan, China. İn a short period of time the virus became an alarming danger for the whole world. Coronavirus has become a nightmare for all the countries. The virus affected many fields. Starting from the worldwide’s economy to the social life and the psychology of human beings. At the time of Corona, we have all seen the importance of true information in times of panic. The topic of our research will be reporting during crises, taking the example of Coronavirus as one of the most recent and mortal health crises. In crises, the media can reach a big audience, becoming the main source of the “approved information”. İt is the main source of information for the majority of citizens. In the Corona crisis, most journalists reporting on different platforms have been in a critical situation while transmitting sensitive information. Since its first appearance, corona had been the topic of thousands of articles with different approaches from the cause of the outbreak to the efforts for finding its treatment and treatment. With the emergence of the Coronavirus outbreak, news about the virus has been followed very much worldwide. Everyone was watching the world's tension and panic caused by the virus. Whether by radio, television, newspaper, or internet, everyone was looking for the right information. The importance of media has increased during the period of Corona. Journalists started to make changes in their writing style, reviewing and reporting the news. Considering this situation, we will focus on the news texts and videos published during the Corona crisis. The Coronavirus outbreak was a challenge not just for the healthcare sector but also for the media. The media sector lived in stress. The workers in the media industry were trying to present sensitive information to the public, using simple ways to make the information clear and understandable. Journalists were obliged to deal with the lack of information and the necessity of ensuring the public doubts and news needs. If any information is misunderstood, the public's behavior may be affected and the result can be very harmful. Based on 2 different countries we will study carefully the media content’s characteristics during corona’s crisis. We will review the news published in Morocco and in France. We will see how channels and media organizations from different countries have made their broadcasting and reporting missions based on the pandemic situation in their countries. To do this, it is essential to fine-tune the news published during the period of Corona.
Keywords: Coronavirus - Covid-19- Fas - Fransa- habercilik - karantina - önlemler -; COVID-19 Pandemic, 2020-; COVID-19 Salgını, 2020-; crisis - news; Fas; France; Fransa; Kitle iletişim araçları; Mass media; Morocco; panik - kriz haberler Coronavirus - Covid-19- Morocco - France- reporting - quarantine - measures - panic -